Coupled Fixed Point Theorems with CLRg property in Fuzzy Metric Spaces . - Dalal, Sumitra (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we prove common coupled fixed point theorems by using E.A. property and CLRg property for coupled mappings without exploiting the notion of continuity, completeness of the whole space or any of its range spaces. Our theorems generalize the result of [5] and [10-14]. We also find an affirmative answer in fuzzy metric space to the problem of Rhoades[2]. Illustrative examples supporting our results have also been cited.